Age increases MCP‐1 level in association with bariatric surgery operating time and metabolic risk severity. (26th April 2017) - Malin, S. K.; Kaplan, J. L.; Meng, L.; Garmey, J. C.; Kirby, J. L.; Taylor, A. M.; Hallowell, P. T.; McNamara, C. A.
Summary: Objective: Assess the role of inflammation on operating time in younger vs. older bariatric surgery patients. Methods: Fifty‐five younger (F: 46, Age: 34.9 ± 4.0 years, body mass index [BMI]: 48.2 ± 1.0 kg m −2 ) and 48 older (F: 34, Age: 57.0 ± 5.1 years, BMI: 46.8 ± 1.0 kg m −2 ) adults were studied prior to surgery. Blood pressure, glycaemic control (fasting glucose/insulin, HbA1c ), lipids (high‐density lipoprotein and triglycerides) and inflammation (monocyte chemoattractant protein‐1 [MCP‐1]) were assessed. Metabolic risk severity z ‐scores were calculated from clinical outcomes. Omental adipose biopsies were collected at surgery for MCP‐1 protein analysis. Operating time was used to characterize surgical difficulty. Results: Older vs. younger adults had higher HbA1c ( P = 0.03). There was no difference in BMI, lipids, metabolic risk severity or insulin between groups, but operating time was longer in older vs. younger individuals ( P = 0.04). Circulating MCP‐1 was also elevated in older vs. younger adults ( P = 0.04) independent of HbA1c, although this was not explained by omental fat. Nevertheless, serum MCP‐1 was associated with increased metabolic risk severity ( R = 0.27, P = 0.01). In addition, operating time was linked to HbA1c ( R = 0.30, P = 0.01) and omental MCP‐1 protein ( R = 0.31, P < 0.01). Conclusions: MCP‐1 is associated with longer operating time and increased metabolic risk severity in older bariatric patients independent of glycaemic control. Pre‐operative treatment of inflammation may be required to enhance surgery effectiveness.